2015
DOI: 10.1039/c5cp01171j
|View full text |Cite
|
Sign up to set email alerts
|

Role of the reaction of stabilized Criegee intermediates with peroxy radicals in particle formation and growth in air

Abstract: We investigate the particle formation mechanism from ozonolysis, and find that it is highly dependent on the structure of the alkene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 100 publications
(225 reference statements)
0
87
2
2
Order By: Relevance
“…Several mechanisms for oligomer product formation in SOA arising from VOC oxidation have been proposed: i) self-and cross-reactions of the peroxy radicals (RO 2 ) (Zhang et al, 2016), ii) reaction of ozonolysis products in the condensed-phase, such as aldol condensation, esterification, hemiacetal and peroxyhemiacetal formation (Ziemann, 2003;Tolocka et al, 2004;Kristensen et al, 2014;Docherty et al, 2005;Muller et al, 2009;Yasmeen et al, 2010;Hall and Johnston, 2012;Witkowski and Gierczak, 2012;DePalma et al, 2013;Lim and Turpin, 2015), iii) dimer cluster formation from carboxylic acids 15 (Hoffmann et al, 1998;Tobias and Ziemann, 2000;Claeys et al, 2009;Camredon et al, 2010;DePalma et al, 2013), iv) reactions of Criegee intermediates (CIs) with VOCs oxidation products (Bonn et al, 2002;Lee and Kamens, 2005;Tolocka et al, 2006;Heaton et al, 2007;Witkowski and Gierczak, 2012;Kristensen et al, 2016;Wang et al, 2016), and vi) reactions of RO 2 radicals with Cis (Sadezky et al, 2008;Zhao et al, 2015). Among them, the reactions of CIs with protic substances (water, alcohols, acids and hydroperoxides) can form ROOH.…”
Section: (A)mentioning
confidence: 99%
“…Several mechanisms for oligomer product formation in SOA arising from VOC oxidation have been proposed: i) self-and cross-reactions of the peroxy radicals (RO 2 ) (Zhang et al, 2016), ii) reaction of ozonolysis products in the condensed-phase, such as aldol condensation, esterification, hemiacetal and peroxyhemiacetal formation (Ziemann, 2003;Tolocka et al, 2004;Kristensen et al, 2014;Docherty et al, 2005;Muller et al, 2009;Yasmeen et al, 2010;Hall and Johnston, 2012;Witkowski and Gierczak, 2012;DePalma et al, 2013;Lim and Turpin, 2015), iii) dimer cluster formation from carboxylic acids 15 (Hoffmann et al, 1998;Tobias and Ziemann, 2000;Claeys et al, 2009;Camredon et al, 2010;DePalma et al, 2013), iv) reactions of Criegee intermediates (CIs) with VOCs oxidation products (Bonn et al, 2002;Lee and Kamens, 2005;Tolocka et al, 2006;Heaton et al, 2007;Witkowski and Gierczak, 2012;Kristensen et al, 2016;Wang et al, 2016), and vi) reactions of RO 2 radicals with Cis (Sadezky et al, 2008;Zhao et al, 2015). Among them, the reactions of CIs with protic substances (water, alcohols, acids and hydroperoxides) can form ROOH.…”
Section: (A)mentioning
confidence: 99%
“…In a third study of SOA from α-pinene ozonolysis, Kidd et al (2014) showed that particles in the 250-500 nm range contained a greater fraction of oligomers, while particles greater than 500 nm contained a greater fraction of monomers. Molecular composition measurements by Zhao et al (2015) of size-selected particles produced by trans-3-hexene ozonolysis showed that particles smaller than 100 nm contained a greater fraction of high-MW oligomers than particles larger than 100 nm. With the exception of Kidd et al, which focused on much larger particle sizes than the rest, the above experiments are consistent with the concept that higher-MW, lower-volatility species formed in the gas phase are more strongly represented in smaller-diameter particles, as would be expected from a condensation-driven process.…”
Section: Introductionmentioning
confidence: 99%
“…As such, certain reagent ions such as metal cations (e.g., Li + , Na + , and K + ) and NH + 4 , which are commonly used for detection of atmospheric organic compounds in offline techniques like electrospray ionization (ESI)-MS (Nizkorodov et al, 2011;Laskin et al, 2012;Witkowski and Gierczak, 2013), have remained largely unavailable for CIMS (Fujii et al, 2001). Compared to I − , NO − 3 , and acetate, which are generally more sensitive to more oxygenated organic compounds than to less oxygenated ones (Aljawhary et al, 2013;Lee et al, 2014;Hyttinen et al, 2015;Iyer et al, 2016;Berndt et al, 2016), these metal cations are expected to be able to sensitively detect both less oxygenated (e.g., compounds containing only carbonyl groups) and highly oxygenated multi-functional organic species (Gao et al, 2010;Nguyen et al, 2010;Nizkorodov et al, 2011;Laskin et al, 2012;Witkowski and Gierczak, 2013;Zhao et al, 2015Zhao et al, , 2016Tu et al, 2016;Zhang et al, 2017), and to form more strongly bound ion adducts. In addition, at present most CIMS techniques use a radioactive ion source such as 210 Po to produce the reagent ions, although more recently some utilize X-ray radiation, electrical discharge (Hirokawa et al, 2009;Yuan et al, 2016), or electron impact (Inomata and Hirokawa, 2017).…”
Section: Introductionmentioning
confidence: 99%